Conceptions of Japan's Security affecting Cooperation with the United Nations - Tsutsui, W (Victoria University of Wellington Law Review, 1997)
This article analyses the vexed question of the interaction of Japan's post-War Constitution, the San Francisco Peace Treaty, and the Japan-US Security Treaty. It compares the initial conceptions of Japanese security in relation to the United Nations with conceptions engendered by the Korean War and more recent peace-keeping operations. It concludes with some implications for Japan's security in a post-Cold War era.